Monitoring the infective process of the downy mildew causal agent within micropropagated rose plants (2012)
Downy mildew in the rose caused by a species of the Peronospora genus is a very restrictive disease for the Colombian greenhouse rose production. The damage observed in the susceptible varieties of commercial rose include symptoms affect young steams and tiny leaves causing reddish and brown spots and defoliation; leading to 10% production losses. The infective behavior of this pathogen was studied with the aim of increasing the knowledge about the biology of the rose downy mildew. The study of the infective process was performed on the Charlotte variety using micropropagated roses inoculated with suspensions of sporangia. A germinal tube was observed during the germination process, it came from a lateral papilla and reached up to 300 microns in length. During this study, the ability of the pathogen to use vascular sieves as communication systems within the plant was determined. Oogonia and antheridia were also observed inside the epidermal cells, and oospores inside the parenchymal tissue close to xylem vessels. To the best of our knowledge, these sexual structures have not been reported on in Colombia before. This study verifies the ability of the downy mildew causal agent to move through the xylem vessels and produce sexual structures, such as oogonia, antheridia and oospores within those tissues.